2014
DOI: 10.1007/s13197-014-1434-3
|View full text |Cite
|
Sign up to set email alerts
|

Steady shear rheological characteristics of model system meat emulsions: Power law and exponential type models to describe effect of corn oil concentration

Abstract: The effect of oil concentration (57.50, 58.75, 60.00 and 61.25 %) and temperature (5, 10 and 15ºC) on steady shear rheological properties of O/W model system meat emulsions were investigated. The effect of temperature and oil concentration was modeled using power law and exponential type functions. The meat emulsions showed non-Newtonian flow behavior because flow behavior index was lower than unity. Consistency coefficient and flow behavior index values of O/W model system meat emulsions were calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…In this respect, in recent years, several studies have been conducted to investigate some flow properties of the model emulsion systems, such as emulsion viscosity (Sarıçoban et al, 2008, 2010, Karaman et al, 2015, apparent yield stress and density (Zorba et al, 2005;Tunçtürk and Zorba, 2006;Kurt, 2006, Gençcelep et al, 2015;Ağar et al, 2016). However, no study has been conducted so far to investigate the texture properties of the model system meat emulsions using Texture Analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, in recent years, several studies have been conducted to investigate some flow properties of the model emulsion systems, such as emulsion viscosity (Sarıçoban et al, 2008, 2010, Karaman et al, 2015, apparent yield stress and density (Zorba et al, 2005;Tunçtürk and Zorba, 2006;Kurt, 2006, Gençcelep et al, 2015;Ağar et al, 2016). However, no study has been conducted so far to investigate the texture properties of the model system meat emulsions using Texture Analyzer.…”
Section: Introductionmentioning
confidence: 99%
“…The cone and plate rheometer was used to determine the apparent viscosity (Karaman, Yilmaz, Kayacier, Dogan, & Yetim, ). This analysis was conducted using TA AR‐G2 rheometer (TA Instruments, New Castle, DE) fitted with a 60 mm and 1° aluminium cone and plate geometry.…”
Section: Methodsmentioning
confidence: 99%
“…The cone and plate rheometer was used to determine the apparent viscosity (Karaman, Yilmaz, Kayacier, Dogan, & Yetim, 2015).…”
Section: Viscositymentioning
confidence: 99%
“…The course of the curves shows that the samples exhibited shear thinning (pseudoplastic) behavior and this generally is in good agreement with previously reported results regarding proteinstabilized emulsions. 16,17 A plausible explanation for this behavior is that increasing shear rate contributed to the breakdown of weak linkages between biopolymers as well as to the arrangement of droplets and biopolymer chains along the flow field, which consequently reduced the resistance to flow. 12,18,19 Starch addition (0.0-50 g kg −1 ) induced increase in shear stress (apparent viscosity, η a ) in both examined systems.…”
Section: Steady-state Shear Rheological Propertiesmentioning
confidence: 99%
“…It was found that with increasing temperature, k values showed a descending trend, most probably due to increased intermolecular distances and consequently reduction in intermolecular forces. 16,26 Experimental data were fitted to an Arrhenius-type equation and the obtained values of activation energy (E a ) and Arrhenius constant (k 0 ) are presented in Table 1. Irrespective of the applied starch type, E a values were negatively correlated with increasing starch concentration (r ≤ −0.987, P < 0.001), whereas k 0 values were positively correlated (r ≥ 0.853, P < 0.05).…”
Section: Steady-state Shear Rheological Propertiesmentioning
confidence: 99%